A novel method to evaluate the community built environment using photographs--Environmental Profile of a Community Health (EPOCH) photo neighbourhood evaluation tool. - Clara K Chow; Daniel J Corsi; Karen Lock; Manisha Madhavan; Pam Mackie; Wei Li; Sun Yi; Yang Wang; Sumathi Swaminathan; Patricio Lopez-Jaramillo; Diego Gomez-Arbelaez; Álvaro Avezum; et al. (PLoS ONE)
Background Previous research has shown that environments with features that encourage walking are associated with increased physical activity. Existing methods to assess the built environment using geographical information systems (GIS) data, direct audit or large surveys of the residents face constraints, such as data availability and comparability, when used to study communities in countries in diverse parts of the world. The aim of this study was to develop a method to evaluate features of the built environment of communities using a standard set of photos. In this report we describe the method of photo collection, photo analysis instrument development and inter-rater reliability of the instrument. Methods/principal findings A minimum of 5 photos were taken per community in 86 communities in 5 countries according to a standard set of instructions from a designated central point of each community by researchers at each site. A standard pro forma derived from reviewing existing instruments to assess the built environment was developed and used to score the characteristics of each community. Photo sets from each community were assessed independently by three observers in the central research office according to the pro forma and the inter-rater reliability was compared by intra-class correlation (ICC). Overall 87% (53 of 60) items had an ICC of ≥ 0.70, 7% (4 of 60) had an ICC between 0.60 and 0.70 and 5% (3 of 60) items had an ICC ≤ 0.50. Conclusions/significance Analysis of photos using a standardized protocol as described in this study offers a means to obtain reliable and reproducible information on the built environment in communities in very diverse locations around the world. The collection of the photographic data required minimal training and the analysis demonstrated high reliability for the majority of items of interest.